A dynamic analysis of in-situ stress state at the Upper Tamakoshi Hydroelectric Project area, Nepal - Panthi, Krishna Kanta; Basnet, Chhatra Bahadur (Hydro Nepal: Journal of Water, Energy and Environment, 2018)
The in-situ stress condition in the rock mass is influenced by both tectonic and geological environment, such as faulting and shearing in the rock mass. This influence is of considerable magnitude in the Himalayan region where the tectonic movement is active, resulting periodic dynamic earthquakes. Each large-scale earthquake causes both accumulation and sudden release of strain energy instigating changes in the in-situ stress environment in the rock mass. This paper evaluates the influence of local shear fault on the in-situ stress state along the shot crete lined high pressure tunnel of Upper Tamakoshi Hydroelectric Project, 456 MW in Nepal. A detailed assessment of the in-situ stress state is carried out by using both; measured data and three-dimensional numerical analysis using FLAC3D. The analysis includes evaluation on the possible changes in the in-situ stress state in the rock mass caused by seismic activities (dynamic loading). HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 23 Year: 2018